2016
DOI: 10.1080/01616412.2016.1187804
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin protects against stroke and increases levels of Notch intracellular domain

Abstract: Curcumin may protect from focal cerebral ischemia reperfusion injury as well as stimulate neurogenesis by activating the Notch signaling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 34 publications
0
34
0
Order By: Relevance
“…Previous studies performed in stroke models have shown that curcumin exerts diverse neuroprotective functions, including antioxidative effects (Thiyagarajan and Sharma, 2004; Yang et al, 2009; Wu et al, 2013), regulation of neuronal (and other cell) apoptosis (Zhao et al, 2008, 2010; Altinay et al, 2017), promotion of mitochondrial biogenesis (Liu et al, 2014), and enhancement of neurogenesis (Liu S. et al, 2016). The present study demonstrates that curcumin reduces ischemic stroke-induced brain damage and improves several functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies performed in stroke models have shown that curcumin exerts diverse neuroprotective functions, including antioxidative effects (Thiyagarajan and Sharma, 2004; Yang et al, 2009; Wu et al, 2013), regulation of neuronal (and other cell) apoptosis (Zhao et al, 2008, 2010; Altinay et al, 2017), promotion of mitochondrial biogenesis (Liu et al, 2014), and enhancement of neurogenesis (Liu S. et al, 2016). The present study demonstrates that curcumin reduces ischemic stroke-induced brain damage and improves several functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin has also been proposed as a promising agent for stroke prevention in humans (Ovbiagele, 2008). Manifold mechanisms are involved in the protective effects of curcumin, including anti-oxidative, anti-inflammatory (Thiyagarajan and Sharma, 2004; Yang et al, 2009; Wu et al, 2013), and anti-apoptotic mechanisms (Zhao et al, 2008, 2010; Altinay et al, 2017), as well as neurogenesis (Liu S. et al, 2016). However, the effect of curcumin on microglial phenotypic polarization after ischemic stroke has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, curcumin has been used in the treatment of cerebrovascular disease due to its good antioxidation and anti-inflammatory effects (Motterlini, Foresti, Bassi, & Green, 2000;Priyadarsini, 1997 pass through the blood-brain barrier of aged rats and is recommended for the prevention and treatment of Alzheimer's disease (Wang et al, 2005;Yang et al, 2005). Nowadays, a number of studies reported that curcumin improves outcomes and attenuates focal cerebral ischemic injury in MCAO rat models (Liu et al, 2016;Miao et al, 2016;Zhao et al, 2010). Similarly, our results showed that curcumin decreased the infarct volume and improved the neurological outcomes in another different MCAO mouse model, which is more and more widely used to investigate the complicated molecular mechanisms of cerebral ischemia in recent years (Evans et al, 2017;H.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, curcumin protected against alcohol-induced neurodegeneration in the hippocampal area [16]. Furthermore, curcumin may stimulate neurogenesis and prevent focal cerebral ischemia reperfusion injury [17]. However, the specific underlying mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 99%